INTEGRATING LOCAL WISDOM IN DIGITAL CHARACTER EDUCATION FOR PRIMARY LEARNERS - Dewi Sawitri (CV. Fahr Publishing, 2024)
This study explores the integration of local wisdom into digital character education for primary school learners, addressing the gap between technological innovation and culturally grounded moral instruction. The objective is to develop a conceptual framework that bridges traditional values with modern learning platforms, promoting ethical development in digital-era classrooms. Using a systematic library research method, this study reviewed 22 peer-reviewed articles and educational reports from 2020 to 2025 across Southeast Asia and other culturally diverse regions. Thematic analysis revealed five dominant strategies in digital values education: digital storytelling, gamified ethical simulations, project-based learning, value-oriented animations, and student-created digital content. The study identified major challenges such as limited teacher competence in digital pedagogy and a lack of localized content, countered by support systems including parent engagement and cultural content adaptation. The novelty of this research lies in its ecosystemic framework that positions learners as active co-creators of moral knowledge, combining cultural narratives with participatory digital tools. Unlike prior models that treat moral instruction as curriculum-driven, this approach emphasizes collaboration between schools, families, and communities in the digital learning process. Findings suggest that digital character education is most effective when it is both technologically engaging and culturally relevant. In conclusion, integrating local wisdom with digital tools offers a promising direction for holistic character formation and global citizenship education in the 21st century.